White knight or partner of choice? The Ukraine war and the role of the Middle East in the energy security of Europe - Mohammad Al-Saidi (5751827) (2023)
The Ukraine war has forced Europe to redefine its energy security policies towards more diversification and less reliance on Russian energy. As an energy-rich and relatively close region, the Middle East can play a potentially important role in Europe's future energy security. However, a short-term and static view on the Middle East's readiness as Europe's energy partner conceals the dynamic nature of Europe's external policy towards this region. Closer energy cooperation with the Middle East requires a holistic approach and informed strategies that consider the realities and perspectives of energy-exporting countries. This paper provides an analysis of the role of the Middle East in Europe's energy security by considering political economic factors such as capacity, domestic reforms, and long-term supply reliability. Using a perspective based on international political economy, long-term strategies for energy cooperation between the Middle East and Europe are highlighted. Integration with North Africa's energy markets and infrastructure can deliver energy supplies and foster energy transition in Europe and the Middle East. Oil diplomacy with Gulf countries is necessary for price stability and the compensation of oil supplies for Europe. Finally, there are opportunities for European countries to strengthen energy trade partnerships (particularly with Qatar) and thus become more involved in the interstate competition for the abundant gas supplies of the Middle East. Europe's energy rapprochement with the Middle East solicits a re-examination of EU external energy policies in order to achieve more long-term and mutually beneficial energy cooperation. Other Information Published in: Energy Strategy Reviews License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.esr.2023.101116